PENGARUH PENERAPAN MODEL PEMBELAJARAN INQUIRI TERHADAP PENINGKATAN HASIL BELAJAR PAI DI SMAN 4 ENREKANG - Salahuddin Abdul Rahman (IAIN Bone, 2021)
This study aims to determine the application of the Inquiry LearningModel, the learning outcomes in Islamic Education (PAI) subjectbefore and after the application of the Inquiry Learning Model, andthe effect of the application of the Inquiry Learning Model on theimprovement of learning outcomes in Islamic education subject ofthe tenth-grade students at SMAN 4 Enrekang. This study applied apre-experimental design in the form of one group pretest-posttestdesign. The results show that: 1) the application of the InquiryLearning Model in Islamic education subject was carried out verywell, 2) the value of the data on learning outcomes in Islamiceducation subject was most students got high score on the pretest.However, it has not reached the minimum mastery criteria. Whereasin the posttest, the learning outcomes of the students at SMAN 4Enrekang were in the high category. That is, the posttest results ofthe tenth-grade students of SMAN 4 Enrekang in learning Islamiceducation subject are high after 4 cycles of treatment arestrengthened by the results of the observation where the averageimplementation of the Inquiry Learning Model is 96.42% which invery good category, and 3) Application of Inquiry Learning Modelhas an effect on improving the learning outcomes in Islamiceducation subject of the tenth-grade students of SMAN 4 Enrekang,Kec. Maiwa Kab. Enrekang.Keywords: Application of Models, Inquiry, Learning Outcome